2013
DOI: 10.3389/fpsyg.2013.00184
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Communication in Speech and Music: The Role of Melodic and Rhythmic Contrasts

Abstract: Many acoustic features convey emotion similarly in speech and music. Researchers have established that acoustic features such as pitch height, tempo, and intensity carry important emotional information in both domains. In this investigation, we examined the emotional significance of melodic and rhythmic contrasts between successive syllables or tones in speech and music, referred to as Melodic Interval Variability (MIV) and the normalized Pairwise Variability Index (nPVI). The spoken stimuli were 96 tokens exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
2
24
0
1
Order By: Relevance
“…The musical protolanguage hypothesis is supported by recent evidence that speech and music share underlying cognitive and neural resources (15)(16)(17)(18)(19)(20)(21)(22), and draw on a common code of acoustic attributes when used to communicate emotional states (23)(24)(25)(26)(27)(28)(29)(30)(31). In their review of emotional expression in speech and music, Juslin and Laukka found that higher pitch, increased intensity, and faster rate were associated with more excited and positive emotions in both speech and music (23).…”
mentioning
confidence: 97%
“…The musical protolanguage hypothesis is supported by recent evidence that speech and music share underlying cognitive and neural resources (15)(16)(17)(18)(19)(20)(21)(22), and draw on a common code of acoustic attributes when used to communicate emotional states (23)(24)(25)(26)(27)(28)(29)(30)(31). In their review of emotional expression in speech and music, Juslin and Laukka found that higher pitch, increased intensity, and faster rate were associated with more excited and positive emotions in both speech and music (23).…”
mentioning
confidence: 97%
“…Probyn's (2000) understanding of the visceral is that 'gut reactions' provide clues to how cultural systems categorise different types of bodies, rendering some comfortable, and others disgusting. We take Probyn's gut reactions to refer to a process that draws attention to the embodied ways -moods, emotions and bodily sensations -that a person inhabits the world.…”
Section: The Viscerality Of Sound and Its Methodological Challengesmentioning
confidence: 99%
“…In short, it has deadening effect' (Simpson, 2008: 821). 1 Studies in psychology and neuroscience have determined that most of the brain is involved in the processing of music and carries information about emotion (Quinto et al, 2013). In addition, the release of hormones such as oxytocin while engaged in music making activities induces strong psychological effects that increase the creation of social bonds (Chanda and Levitin, 2013; Tarr et al, 2014).…”
Section: Rhythmanalysis and Soundscapesmentioning
confidence: 99%
See 1 more Smart Citation
“…Melodik aralık değişkenliğini ve ardışık seslerin ikili zamansal değişkenliğini temel alarak, ardışık heceler veya sesler arasındaki melodik ve ritmik zıtlıkların emosyonel anlamını inceleyen çok yeni bir araştırmada, konuşma ve müzik iş-lemleri arasında daha önce bilinmeyen bazı yeni farklılıklar ortaya konulmuştur. 19 Bu yeni verilere göre, müzikte ve konuşmada emosyon ileten akustik ipuçları farklıdır. Formal müzik; harmoni (uyum) ve ses perdelerinin belli kurallara göre dizilimini sağlayan tonal hiyerarşi gibi kendi yapısına özgü boyutlar içermektedir.…”
Section: Tartişma Ve Sonuçunclassified